French mission “arabian seashores”: The desert project “exploring the omani rub’ al khali” (december 2022) - Charpentier, Vincent; Maiorano, Maria Pia (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The French mission “Arabian Seashores” has been exploring the Omani coast of the Arabian Sea since 2010. The team has prospected, surveyed various sites, and conducted excavations at Khuwaymah, Masirah Island, Hallaniyat Archipelago, Sharbithat, Hasik as well as other sites along the coast. Additionally, they have explored the Jebel Qara and several rock art sites. The mission’s research focuses on the chronology of the Final Paleolithic to the Early Bronze Age, spanning the period between 10,000 and 2000 BCE. Specifically, their attention is on the transition from the Paleolithic to the Neolithic era, marking the shift from predatory societies to the first productive communities. The mission has made significant discoveries, including the Final Paleolithic cave of Natif and the Neolithic sites of Ad-Dahariz (Salalah), Hasik, and Sharbithat. Simultaneously, a project in the Rub’ Al Khali desert was carried out in collaboration with a team of geologists and paleontologists. During the latest mission in December 2022, particular emphasis was placed on research in this area, confirming the extraordinary potential of these sites. The campaign played a critical role in enhancing our understanding of cultural transfer, settling patterns, and technological innovation in Southern Arabia during the Neolithic period. Overall, the project has expanded our current knowledge of Neolithic cultures in desert locations by conducting an integrated study of the paleoenvironment and a techno-quantitative examination of the lithic industries. This work lays the foundation for future research in this field.
Keywords: Archéologie -- Oman

Archaeological expedition to al khashbah (2023): Al khashbah KHS-a - Schmidt, Conrad; Maiorano, Maria Pia; Proctor, Lucas (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Several locations north of the village of Al Khashbah have yielded Neolithic remains, most likely due to the area’s accessible chert outcrops and elevated fluvial terrace systems overlooking wadi floodplains. KHS-A, the main Neolithic site in the area, is distinguished by extensive flint scatters, isolated stone constructions, and fireplaces. In 2022, the team excavated a preliminary test trench (KHS-A.1) that yielded a high number of lithics and charcoal samples. Radiocarbon dating placed the age of the complex within the Late Neolithic Period. In 2023, further excavations at KHS-A.13 were undertaken with the goal of confirming the age dating of the site and expanding our understanding of the extent and occupational sequence of the KHS-A complex. The trench consisted of a 3 × 4 m exposure revealing multiple fireplaces, ash pits, and post holes. The investigation of the Neolithic occupations at Al Khashbah seeks to open new routes and further perspectives in the study of Early and Middle Holocene in the broad area between the mountains and the Rub Al Khali desert.
Keywords: Archéologie -- Oman

L'industrie lithique des premiers chasseurs-collecteurs maritimes d'Arabie : la grotte de Natif 2 (Dhofar, sultanat d'Oman) - Marchand, Gregor; Charpentier, Vincent; Maiorano, Maria Pia; Borgi, Federico (Bulletin de la Société préhistorique française, 2024)
Découverte en 2013, dans le Dhofar-province méridionale du sultanat d'Oman-la grotte de Natif 2 est actuellement l'unique témoin de communautés maritimes du Paléolithique final, en péninsule Arabique. La fouille d'une partie du porche révèle une importante activité humaine entre le début du IX e et le milieu du VIII e millénaire avant notre ère, notamment en termes de production halieutique, d'écologie ou de technologie lithique. Ainsi la pêche pratiquée dans des eaux peu profondes et à quelques centaines de mètres de la grotte, s'oriente vers de petites espèces pélagiques (anchois et sardinelles), mais aussi d'un petit poisson-chat marin. En parallèle, la capture de raies et de squales (ces derniers pouvant dépasser plus de 2 m de long), est confirmée. Cet article présente les industries lithiques datées de la première moitié du VIII e millénaire avant notre ère (env. 7950-7600 cal. BCE). L'étude vise à caractériser les techniques et méthodes de débitage, afin de compléter nos faibles connaissances sur les technocomplexes dits « à pointe de Fasad ». L'analyse typologique et technologique de l'industrie lithique de Natif 2 montre une grande homogénéité dans l'en-semble de la stratigraphie. Les armatures de Fasad sont surtout très homogènes dans leurs principes techniques. La production de lamelles à profil longitudinal peu convexe-voire rectiligne-et à extrémité distale pointue constitue un objectif de débitage original, qui a, de facto, valeur de marqueur culturel. Les autres outils aménagés les plus caracté-ristiques se composent de troncatures obliques sur lames ou éclats, de perçoirs et d'éclats denticulés. Pour de tels outils assez courts, les méthodes de production observées sont très simples, avec une production intégrée de lames courtes, de lamelles épaisses et d'éclats non corticaux.
Keywords: Archéologie -- Oman

The first collective Neolithic megalithic tomb in Oman - Danielisová, Alžběta; Maiorano, Maria Pia; Šneberger, Jiří; Ackerman, Lukáš; Daněček, David; Garba, Roman; Martinez-Garcia, Alfredo; Lüdecke, Tina (Antiquity, 2025)
, A newly discovered grave in Wadi Nafūn, Oman, features a unique burial structure, combining monumental architecture and the collective deposition of human remains from multiple Neolithic groups. Detailed analysis of the burial community reveals new insights into Neolithic rituals and subsistence strategies during the Holocene Humid Period in southern Arabia.
Keywords: Archéologie -- Oman